Analisis Mutu Pendidikan Islam Melalui Lensa Teori Transendensi Viktor Frankl: Mencari Makna Mutu Melampaui Standar Akreditasi - Prasetiyo, Aldi; Aimah, Siti (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ANALYSIS OF THE QUALITY OF ISLAMIC EDUCATION THROUGH THE LENS OF THE TRANSCENDENCE THEORY OF VIKTOR FRANKL: SEARCHING FOR THE MEANING OF QUALITY BEYOND ACCREDITATION STANDARDSThe quality of Islamic education has tended to be understood narrowly through administrative indicators and formal accreditation achievements, while the dimensions of meaning, values, and transcendental goals of education have not been a primary concern. The dominance of the managerial-technocratic paradigm has resulted in quality assessments being more oriented towards documents, standards, and academic achievements, resulting in a lack of systematic measurement of meaningful learning experiences and the internalization of students' spiritual values. This study aims to analyze the quality of Islamic education through the perspective of Viktor Frankl's transcendence theory, emphasizing the meaning of life, moral responsibility, and spiritual awareness as the core of educational quality. The study used a descriptive qualitative approach with a case study method at SMK Darussalam Blokagung. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using the Miles, Huberman, and Saldana model. The results indicate a gap between administrative quality and substantive quality of education. Although the school has met formal accreditation standards, learning is still oriented towards academic and administrative targets, with minimal integration of transcendental values into learning practices. This study finds that Viktor Frankl's theory of transcendence has strategic potential for reconstructing a more holistic concept of Islamic education quality, by integrating formal standards and meaningful learning experiences. Thus, the quality of Islamic education is measured not only by compliance with accreditation standards but also by the success of education in shaping spiritually and morally meaningful individuals.